Pseudomonas sivasensis 2RO45 inoculation alters the taxonomic structure and functioning of the canola rhizosphere microbial community - Świątczak, Joanna; Kalwasińska, Agnieszka; Szabó, Attila; Swiontek Brzezinska, Maria (Frontiers in Microbiology, 2023)
Inoculation with plant growth-promoting rhizobacteria (PGPR) is an eco-friendly sustainable strategy for improving crop productivity in diverse environments under different conditions. Our earlier study demonstrated that Pseudomonas sivasensis 2RO45 significantly stimulated canola (Brassica napus L. var. napus) growth. The aim of the present study was to investigate the structural and functional dynamics in the canola rhizosphere microbiome after inoculation with PGPR P. sivasensis 2RO45. The results based on alpha diversity metrics showed that P. sivasensis 2RO45 did not significantly alter the diversity of the native soil microbiota. However, the introduced strain modified the taxonomic structure of microbial communities, increasing the abundance of plant beneficial microorganisms, e.g. bacteria affiliated with families Comamonadaceae, Vicinamibacteraceae, genus Streptomyces, and fungi assigned to Nectriaceae, Didymellaceae, Exophiala, Cyphellophora vermispora, and Mortierella minutissima. The analysis of community level physiological profiling (CLPP) revealed that microbial communities in the P. sivasensis 2RO45 treated canola rhizospheres were more metabolically active than those in the non-treated canola rhizosphere. Four carbon sources (phenols, polymers, carboxylic acids, and amino acids) were better metabolized by the microbial communities from the rhizosphere of plants inoculated with the P. sivasensis 2RO45 than non-inoculated canola rhizospheres. Based on the community-level physiological profiles, the functional diversity of the rhizosphere microbiome was altered by the P. sivasensis 2RO45 inoculation. Substrate utilization Shannon diversity (H) index and evenness (E) index were significantly increased in the treated canola plants. The study provides new insight into PGPR-canola interactions for sustainable agriculture development.